Analisis SIA Berupa POS PBB Terhadap Pemberian Keringanan Wajib Pajak Pada BPKAD Kota X - Dwikamba, Javier Erlandaffa Satria; Neni Meidawati (Program Sarjana Terapan Universitas Islam Indonesia, 2023)
This study aims to determine the efficiency of using an accounting information system (AIS) in the form of a payment online system for land and building tax (POS PBB) for providing taxpayer relief. The research conducted is descriptive research with a qualitative approach. The sources and data for this research were obtained from the BPKAD kota Yogyakarta. The research data in this study were interviews and observation as primary data and documents as secondary data. results of the analysis of this study, can be concluded that the Analysis of AIS in the Form of Using POS PBB for the Provision of Taxpayer Relief at BPKAD Kota Yogyakarta is running well and efficiently, and the provision of menus by the activities of providing PBB relief to taxpayers makes it easier reviewers in reviewing existing relief files. Even though the use of the PBB POS application is efficient, problems with using the application can still be found, both in the form of system errors and human errors. To minimize these obstacles, BPKAD Kota Yogyakarta made efforts in the form of procurement of hardware and software; training for work units; and collaboration with the internal and external parts of BPKAD kota Yogyakarta.